Global Legal Issues Concerning Patentability of Phage-Based Therapeutics - Aidonojie, Paul Atagamen; Aidonojie, Esther Chetachukwu; Obieshi, Eregbuonye; Hassan, Adebowale; Okpoko, Mercy Osemudiame (Universitas Brawijaya, 2026)
Phage-based therapeutics offer a promising solution to the growing global threat of multidrug-resistant bacterial infections. However, the patentability of these biologics faces significant legal problems due to varying international standards and the challenge of distinguishing naturally occurring phages from patentable inventions. This legal uncertainty hampers innovation, investment, and the global development of phage therapies. This study therefore examines global laws regarding the patentability of phage-based therapeutics and the existing legal gap. The doctrinal approach, which is widely used, relies heavily on primary and secondary materials. The research analysis found that phage-based therapeutics are considered an invention for biomedical use as an alternative to antibiotic-resistant diseases; however, there are inconsistencies in how jurisdictions treat phage patent applications. In this regard, the international laws that ought to harmonise and close this loophole seem inadequate. Furthermore, the study observes that existing international laws do not specifically address phage-based therapeutic inventions. Also, the criteria for obtaining a patent under international law seem complex, as member states are the final decision-making bodies for granting patents, including for phage-based therapeutic inventions. The study, therefore, concludes that establishing clear legal frameworks and harmonising international standards would require a great deal of time to achieve phage protection while also pursuing public health goals. This will, in turn, result in regulatory support that would ensure finding a fine balance between obtaining a patent and therapeutic accessibility.